Конкурентні стратегії на ринку туристичних послуг України - Колокольчикова, Ірина Володимирівна; Колокольчикова, Ирина Владимировна; Kolokolchykova, Iryna (My University, 2020)
UK: У статті обґрунтована необхідність застосування стратегічного мислення при розвитку ринкової діяльності у сфері туристичних послуг. Визначено, що стратегічне мислення та прогнозування виробничих процесів на туристичному ринку є запорукою витримки конкурентної боротьби між його операторами. Встановлено, що процес планування передбачає врахування усіх факторів, які оказують вплив на діяльність туристичних фірм, особливе місце відводиться менеджменту та кадрової підготовки фахівців. Надлишок наявної інформації відіграє негативну роль у формуванні перспективних напрямів діяльності. Обґрунтовано, що в сучасних умовах Україна має невичерпний потенціал щодо розвитку туристичного бізнесу та освоєння його сегментів. Аналіз статистичних даних показує змістовні зрушення щодо кількості відпочиваючих та напрямів і характеру відпочинку. Кількісні показники впливають на фінансові показники. Встановлено, що у діяльності туристичних фірм на ринку цих послуг доцільно застосовувати конкурентні стратегії. Серед таких стратегій визначена: стратегія лідирування за витратами, стратегія диференціації та стратегія фокусування. Відображено прояви та характерні риси застосування кожної зі стратегій на туристичному ринку. Проаналізовано показники, на які орієнтована стратегія розвитку туризму та курортів, що підтверджує доцільність та обґрунтованість застосування конкурентних стратегій для розвитку туристичного бізнесу. EN: Modern life events and globalization processes that are taking place around the world have given impetus to the development of business in the service sector. A large number of the working population, which was previously engaged in production, is now declining. Automation and informatization of all life and production processes allows a person to reorient in the areas of their professional activities and forms of recreation. Today, most of the working population is involved in the creation and provision of services. The market of tourist services is the most promising; the demand for it is formed daily and has a constant and special nature of orders, so the offers become diverse. However, with increasing competition, the development of its market is complicated by the slowdown in the formation of customer bases, and therefore requires the use of appropriate strategies to develop all segments and marketing niches. Purpose. Substantiation of the need for strategic thinking in the implementation of production activities in the market of tourist services, analysis of current trends and existing competitive strategies that is inherent in each segment. Operators of the market of tourist services, as well as the availability and feasibility of applying competitive strategies. Results. The study substantiates that it is impossible only by simple planning of their own activities to withstand competition in the market, retain their customers, gain a large customer bas and get a stable income for continued existence and growth. The planning process does not anticipate rapid changes and the impact of factors that over time either increase or transform, which complicates production processes. In today's market conditions, a more effective mechanism for effective management of the production process is forecasting, which takes into account and attempts to predict the strength of external and internal factors influencing the market, allows staff to think systematically and take into account the intuitive vision of complex issues. In essence, we are talking about cognitive planning of tourism activities in accordance with the list of services that will be in constant demand. The strategy of leading the market of tourist services is implemented by reducing costs or prices for services. This strategy in Ukraine is used by those travel agencies that either begins their careers or in the process of developing new travel services, creating new markets and new customers. The diversification strategy is the engine of any progress, and the travel services market is no exception. Urbanization and globalization, lifestyle changes and other perceptions of the world require tour operators to find new competitive offers. The strategy of focusing on the development of the market of tourist services is essentially an in-depth specialization, focus on a specific niche, namely the target group of customers of tourist services, or geographical concentration. In this aspect, it is interesting that when considering domestic tourism, the market of tourist services is more often focused on regions that differ in zone features, cultural monuments and other objects. Tourists of the domestic market consciously go on vacation to the region, which in their imagination has some differences from another region Originality. The tools of strategic planning of operators in the tourism market are identified, namely: 1) competitive strategies that embody and take into account the differences between service customers, markets, segments, prices and other offers; 2) management of organizations and staff, which is a powerful motivator and implementer of strategic goals; 3) economic indicators for assessing both quantitative and qualitative parameters of the service sector, expanding the range and attracting additional customers; 4) formation of client bases and development of marketing offers with definition of advantages in the price of service or focusing on innovative tendencies of the offer of tourist services. All this together gives a strategic idea of the development of the market of tourist services and the basis for choosing one of the existing competitive strategies. Conclusion. All the above arguments prove the need for strategic thinking and orientation of the domestic market of tourist services on forecasting and cognitive modelling of processes. It is also proved that Ukrainian tour operators have all the grounds and tools to use competitive strategies in planning their own business. And Ukraine has great potential and underdeveloped niches in the market of tourist services and is an attractive focus for foreign tourists. Such approaches to the organization of the tourism business will allow developing both domestic and foreign tourism, to compete with other operators in this market.
Competitive strategies in the market of tourist services of Ukraine
Keywords: ринок туристичних послуг; попит та пропозиція; стратегія лідирування; стратегія диференціації; стратегія фокусування; сегмент ринку; інновація; tourism services market; supply and demand; leadership strategy; differentiation strategy; focus strategy; market segment; innovation